Comparative study of microfacies variation in two samples from the Chittenango member, Marcellus shale subgroup, western New York state, USA - Balulla, S. (American Institute of Physics Inc., 2015)
This study demonstrates the significant lithologic variations that occur within the two shale samples from the Chittenango member of the Marcellus shale formation from western New York State in terms of mineralogical composition, type of lamination, pyrite occurrences and fossil content using thin section detailed description and field emission Scanning electron microscope (FESEM) with energy dispersive X-Ray Spectrum (EDX). This study is classified samples as laminated clayshale and fossiliferous carbonaceous shale. The most important detrital constituents of these shales are the clay mineral illite and chlorite, quartz, organic matter, carbonate mineral, and pyrite. The laminated clayshale has a lower amount of quartz and carbonate minerals than fossiliferous carbonaceous shale while it has a higher amount of clay minerals (chlorite and illite) and organic matter. FESEM analysis confirms the presence of chlorite and illite. The fossil content in the laminated clayshale is much lower than the fossiliferous carbonaceous shale. This can provide greater insights about variations in the depositional and environmental factors that influenced its deposition. This result can be compiled with the sufficient data to be helpful for designing the horizontal wells and placement of hydraulic fracturing in shale gas exploration and production. Â© 2015 AIP Publishing LLC.